2021
DOI: 10.1177/2473974x211046598
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3‐Dimensional Middle Ear Model to Teach Anatomy and Endoscopic Ear Surgical Skills

Abstract: Mastery of ear anatomy and otologic surgical skills is challenging for trainees, and educational resources are limited. Advancements in 3-dimensional (3D) printing have enabled the construction of complex microscopic models. Otoendoscopy provides excellent visualization and has been shown to enhance anatomic learning. Our aim was to develop a 3D model of the middle ear and external auditory canal using computed tomography images of a pediatric temporal bone for use with otoendoscopes. Resulting models are life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To our knowledge, there are currently no other high-fidelity (HF) middle ear simulators that have established construct and content validity (19,20,23). A comprehensive review of the literature identified models meant to solely mimic anatomy without functional fidelity, modified cast-produced artificial models, research prototypes, and low-fidelity (LF) models made with readily available materials (19,(23)(24)(25)(26)(27)(28). Previously, we reported preliminary studies demonstrating face (29) and content validity (30) of an HF, inexpensive, three-dimensional printed surgical middle ear simulator (SMS).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are currently no other high-fidelity (HF) middle ear simulators that have established construct and content validity (19,20,23). A comprehensive review of the literature identified models meant to solely mimic anatomy without functional fidelity, modified cast-produced artificial models, research prototypes, and low-fidelity (LF) models made with readily available materials (19,(23)(24)(25)(26)(27)(28). Previously, we reported preliminary studies demonstrating face (29) and content validity (30) of an HF, inexpensive, three-dimensional printed surgical middle ear simulator (SMS).…”
Section: Introductionmentioning
confidence: 99%